On Reconstitution of Bacterial Photophosphorylation In Vitro - Garcia, Augusto F. (1974)
Membranes active in oxidative phosphorylation but inactive in photophosphorylation were isolated from a carotenoid-less and bacteriochlorophyll-less mutant strain of Rhodopseudomonas capsulata. These membranes were uncoupled and recombined with coupling factor from the same strain and with reaction centers from a photosynthetically active revertant strain. The reconstituted system was able to form ATP from ADP and inorganic phosphate under anaerobic conditions in the light. Rates of 2 nmoles of ATP formed per min per μg of bacteriochlorophyll were obtained. A high incorporation of (32)P from inorganic phosphate into ADP in the light as well as in the dark was observed, the activity of which was associated with coupling factor. This incorporation occurs both aerobically and anaerobically and appears to be independent of photophosphorylation.